Implementasi Website Laundry Digital Untuk Meningkatkan Efisiensi Pelayanan - Trisnayanti, Ni Nyoman; Mulianingsih, Ni Luh Putu Eka; Puspitasari, Ni Kadek Dwi; Dasi, Ni Putu Laksmi Priya Dewi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
Administrative activities at Srikandi Laundry previously relied on separate manual records for customer information, service transactions, operational expenses, and financial reporting. This approach often increased processing time, made data retrieval less practical, and complicated the preparation of operational reports. To overcome these challenges, an integrated web-based information system was designed to support the operational activities of the laundry business. The application combines customer data management, regular and package laundry transaction processing, expense recording, invoice generation, and report preparation within a single platform, enabling business processes to be carried out more efficiently. The software development followed the Waterfall approach, beginning with requirement analysis, followed by system design, implementation, and functional evaluation. The application was implemented using PHP and MySQL, while the system design employed Use Case Diagrams, Flowcharts, and an Entity Relationship Diagram (ERD). System functionality was evaluated through Black Box Testing on the main features of the application. All test scenarios produced the expected outputs, resulting in a functional success rate of 100%. The implementation indicates that the system simplifies administrative tasks, improves transaction recording accuracy, accelerates data retrieval, and supports daily operational activities at Srikandi Laundry.